Basal metabolic rate and body composition of elite Japanese male athletes - Koshimizu, T.; Matsushima, Y.; Yokota, Y.; Yanagisawa, K.; Nagai, S.; Okamura, K.; Komatsu, Y.; Kawahara, T. (The Journal of Medical Examination, 2012)
The estimated energy requirement is important for adequate nutritional management in athletes. The energy requirement can be estimated from the basal metabolic rate (BMR). However, there is little data regarding the BMR of Japanese athletes. This study measured the BMR and body composition of 81 elite Japanese male athletes in different sports categories: endurance (E), strength, power and sprint (S) and ball game (B). The factors influencing the BMR were also investigated. The BMR and body composition were measured by indirect calorimetry and an air-displacement plentysmograph device (the BOD POD), respectively. The BMR per lean body mass (LBM) differed significantly among the three groups. The BMR was significantly correlated with the body weight (BW) and LBM in all groups. A multiple-regression analysis showed that the LBM was the most powerful predictor in the E and S groups, whereas the BW was the most powerful predictor in the B group. The BW appears to become an important predictor as the BW of athletes increases. Additionally, height was the second explanatory variable in the S and B groups, thus suggesting that height needs to be considered for the BMR in these groups. Therefore, the BMR in elite athletes needs to be estimated according to their body composition.